2017
DOI: 10.24246/josse.v1i2p1-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of the dregs of green tea leaves (Camellia sinensis L.) on Staphylococcus epidermidis as causes of acne

Abstract: The dregs of green tea leaves have not been used until today, it is still considered as a waste that is not useful. It is known that the dregs of the green tea leaves contain Epigallocatechin-3-gallate (EGCG), which is quite high. EGCG has benefits as an antibacterial. The long-term goal of this research is the application of cosmetic preparation products from the dregs of green tea leaves that have effectiveness, stability and high economic value. The specific target of this research is to get the dose and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Research by Widyaningrum et al (2017) showed that EGCG levels in green tea leaf pulp are 21.325% w/w while EGCG levels in green tea leaf are 60.98% w/w (Widyaningrum et al, 2015a). This indicates that the concentration of EGCG in green tea leaf is greater than that of in its waste.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Widyaningrum et al (2017) showed that EGCG levels in green tea leaf pulp are 21.325% w/w while EGCG levels in green tea leaf are 60.98% w/w (Widyaningrum et al, 2015a). This indicates that the concentration of EGCG in green tea leaf is greater than that of in its waste.…”
Section: Discussionmentioning
confidence: 99%
“…Green tea leaf waste has not been utilized. Based on preliminary studies, green tea leaf waste still contain EGCG although not as much as the first processed green leaf tea (Widyaningrum, 2017). Waste based product are expected to reduce the cost of production to benefit the middle society without reducing its quality and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus (Trisina et al, 2021). (Savira & Suharsono, 2013;Widyaningrum et al, 2017;Herwin et al, 2018). Previous research has established a cream formulation from 96 % ethanol extract of green tea pulp in a multiple emulsion formula that has good physical qualities and antibacterial activity and may be utilized as a reference for formulation (Widyaningrum, 2017;Karmilah, 2021).…”
Section: Propionibacterium Acnes Andmentioning
confidence: 99%